Fierce self-compassion : how women can harness kindness to speak up, claim their power, and thrive - Neff, Kristin (HarperWave, an imprint of HarperCollinsPublishers, 2021)
Drawing on research, her personal life story and empirically supported practices, the author of Self-Compassion shows women how to reclaim balance within themselves and use fierce and tender self-compassion to ensure their own wholeness and well-being.